Sine ventilation in lung injury models: a new perspective for lung protective ventilation - Spassov, Sashko (Sci Rep, 2020)
Mechanical ventilation is associated with the risk of ventilator induced lung injury. For reducing lung injury in mechanically ventilated patients, the application of small tidal volumes and positive end-expiratory pressures has become clinical standard. Recently, an approach based on linear airway pressure decline and decelerated expiratory flow during expiration implied lung protective capacities. We assumed that ventilation with a smoothed, i.e. sinusoidal airway pressure profile may further improve ventilation efficiency and lung protection. We compared the effects of mechanical ventilation with sinusoidal airway pressure profile (SINE) regarding gas exchange, respiratory system compliance and histology to conventional volume and pressure controlled ventilation (VCV and PCV) and to VCV with flow-controlled expiration (FLEX) in two rat models of lung injury, tween induced surfactant depletion and high tidal volume mechanical ventilation. In both lung injury models ventilation with SINE showed more efficient CO(2) elimination and blood oxygenation, improved respiratory system compliance and resulted in lower alveolar wall thickness, compared to VCV, PCV and FLEX. Optimization of the airway pressure profile may provide a novel means of lung protective mechanical ventilation.